Deep carbon through time: Earth's diamond record and its implications for carbon cycling and fluid speciation in the mantle. (15th April 2020) - Howell, D.; Stachel, T.; Stern, R.A.; Pearson, D.G.; Nestola, F.; Hardman, M.F.; Harris, J.W.; Jaques, A.L.; Shirey, S.B.; Cartigny, P.; Smit, K.V.; Aulbach, S.; et al.
Abstract: Diamonds are unrivalled in their ability to record the mantle carbon cycle and mantle f O2 over a vast portion of Earth's history. Diamonds' inertness and antiquity means their carbon isotopic characteristics directly reflect their growth environment within the mantle as far back as ∼3.5 Ga. This paper reports the results of a thorough secondary ion mass spectrometry (SIMS) carbon isotope and nitrogen concentration study, carried out on fragments of 144 diamond samples from various locations, from ∼3.5 to 1.4 Ga for P [peridotitic]-type diamonds and 3.0 to 1.0 Ga for E [eclogitic]-type diamonds. The majority of the studied samples were from diamonds used to establish formation ages and thus provide a direct connection between the carbon isotope values, nitrogen contents and the formation ages. In total, 908 carbon isotope and nitrogen concentration measurements were obtained. The total δ 13 C data range from −17.1 to −1.9 ‰ (P = −8.4 to −1.9 ‰; E = −17.1 to −2.1‰) and N contents range from 0 to 3073 at. ppm (P = 0 to 3073 at. ppm; E = 1 to 2661 at. ppm). In general, there is no systematic variation with time in the mantle carbon isotope record since > 3 Ga. The mode in δ 13 C of peridotitic diamonds has been at −5 (±2) ‰ since the earliest diamond growth ∼3.5 Ga, and this mode is also observed in the eclogitic diamond record since ∼3 Ga. The skewness of eclogitic diamonds' δ 13 C distributions to more negative values, which the data establishes began around 3 Ga, is also consistent through time, with no global trends apparent. No isotopic and concentration trends were recorded within individual samples, indicating that, firstly, closed system fractionation trends are rare. This implies that diamonds typically grow in systems with high excess of carbon in the fluid (i.e. relative to the mass of the growing diamond). Any minerals included into diamond during the growth process are more likely to be isotopically reset at the time of diamond formation, meaning inclusion ages would be representative of the diamond growth event irrespective of whether they are syngenetic or protogenetic. Secondly, the lack of significant variation seen in the peridotitic diamonds studied is in keeping with modeling of Rayleigh isotopic fractionation in multicomponent systems (RIFMS) during isochemical diamond precipitation in harzburgitic mantle. The RIFMS model not only showed that in water-maximum fluids at constant depths along a geotherm, fractionation can only account for variations of <1‰, but also that the principal δ 13 C mode of −5 ± 1‰ in the global harzburgitic diamond record occurs if the variation in f O2 is only 0.4 log units. Due to the wide age distribution of P-type diamonds, this leads to the conclusion that the speciation and oxygen fugacity of diamond forming fluids has been relatively consistent. The deep mantle has therefore generated fluids with near constant carbon speciation for 3.5 Ga.